1999
DOI: 10.1046/j.1537-2995.1999.39499235665.x
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of errors in blood component transfusion records with regard to quality improvement of data acquisition and to the performance of lookback and traceback procedures

Abstract: A remarkably high frequency of discrepancies exists between computerized blood bank records and the information recorded on returned blood transfusion forms. The processes of data acquisition and entry must be included in quality assurance efforts in transfusion medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…Patient safeguards to prevent mistransfusion are inadequate. Previous published studies have repeatedly documented weaknesses in performance of the bedside clerical check 18‐20 . Of particular concern is the suggestion that the process has likely eroded in recent decades, perhaps due to increasing patient‐to‐nurse ratios, elimination of specialty nursing teams responsible for administering blood, shorter lengths of stay in hospital, higher nursing turn‐over rates, and other unrecognized factors.…”
Section: Unsafe At Any Speed: Three Dangerous Focal Points In the Tramentioning
confidence: 99%
“…Patient safeguards to prevent mistransfusion are inadequate. Previous published studies have repeatedly documented weaknesses in performance of the bedside clerical check 18‐20 . Of particular concern is the suggestion that the process has likely eroded in recent decades, perhaps due to increasing patient‐to‐nurse ratios, elimination of specialty nursing teams responsible for administering blood, shorter lengths of stay in hospital, higher nursing turn‐over rates, and other unrecognized factors.…”
Section: Unsafe At Any Speed: Three Dangerous Focal Points In the Tramentioning
confidence: 99%
“…However, trying to design human error out of the system by increasing computerization solves one set of problems but breeds a new generation of others (Sheridan & Thompson, 1994). This is evidenced in a study which compared information issued by the blood bank computer system and written information on transfusion reports returned to the blood bank from the wards (Zimmerman et al , 1999). Results showed that discrepant information in the recipient's identity and the blood component status occurred in 1·24% of transfusion data records reviewed, or 1 in every 81 transfusions (n = 49 224 transfusions).…”
Section: Errors Critical Incidents and Near Misses In Transfusion Mementioning
confidence: 99%
“…However, in the entire investigated population as well as the analyzed subgroup suffering from shock on admission, the presence of a blood bank, associated with an increased frequency of transfusions, did not improve survival. Because of the lack of mortality reduction and considering the risks and costs of each blood transfusion [37, 38], the indication for transfusion in severely injured patients warrants critical evaluation. The easy availability of blood products should not influence clinical decision making.…”
Section: Discussionmentioning
confidence: 99%